Um método para avaliar a taxa de corrosão - Vaz, Ednilson Luiz Silva [UNESP]; Acciari, Heloisa Andréa [UNESP]; Codaro, Eduardo Norberto [UNESP] (Sociedade Brasileira de Química, 2011)
In this paper it is proposed an indirect method to evaluate the corrosion rate of an aluminum and zinc alloy in alkaline solution by using a well-known device for collecting gases over water. The hydrogen gas formation, a corrosion product, is monitored at different time intervals and associated with the alloy mass loss. It has been suggested that the students should work in groups, which may make feasible the social interaction among them and that results discussion may be done collectively under a professor orientation. This proposal may propitiate the learning of terminology and involved concepts as well as contribute to a better understanding of corrosion phenomena that occur in their everyday life.
A method for corrosion rate evaluation
Keywords: chemistry education; corrosion; social interaction